Flèche d’Or by Django Reinhardt: why was it not heard? (Per Musi, 2014)
This article presents a criticism on historic aspects of the environment around the session of the tune Flèche d’Or by Django Reinhardt, and how critics considered the French musician at his time, both in America and Europe. After the demonstration that this piece is a true earlier example of what was considered the flame of the so called “modal jazz” with Miles Davis, the question takes place: Why was it not heard?